Locally resolved stress-state in samples during experimental deformation: insights Into the effect of stress on mineral reactions - Cionoiu, Sebastian; Moulas, Evangelos; Stünitz, Holger; Tajcmanová, Lucie (Journal of geophysical research. Solid earth, 2022)
Understanding conditions in the Earth's interior requires data derived from laboratory experiments. Such experiments provide important insights into the conditions under which mineral reactions take place as well as processes that control the localization of deformation in the deep Earth. We performed Griggs-type general shear experiments in combination with numerical models, based on continuum mechanics, to quantify the effect of evolving sample geometry of the experimental assembly. The investigated system is constituted by CaCO3 and the experimental conditions are near the calcite-aragonite phase transition. All experimental samples show a heterogeneous distribution of the two CaCO3 polymorphs after deformation. This distribution is interpreted to result from local stress variations. These variations are in agreement with the observed phase-transition patterns and grain-size gradients across the experimental sample. The comparison of the mechanical models with the sample provides insights into the distribution of local mechanical parameters during deformation. Our results show that, despite the use of homogeneous sample material (here calcite), stress variations develop due to the experimental geometry. The comparison of experiments and numerical models indicates that aragonite formation is primarily controlled by the spatial distribution of mechanical parameters. Furthermore, we monitor the maximum pressure and sigma(1) that is experienced in every part of our model domain for a given amount of time. We document that local pressure (mean stress) values are responsible for the transformation. Therefore, if the role of stress as a thermodynamic potential is investigated in similar experiments, an accurate description of the state of stress is required.